American heiress [large type] : the wild saga of the kidnapping, crimes and trial of Patty Hearst - Toobin, Jeffrey (Random House Large Print, 2016)
On February 4, 1974, Patty Hearst, a sophomore in college and heiress to the Hearst family fortune, was kidnapped by a ragtag group of self-styled revolutionaries calling itself the Symbionese Liberation Army. The already sensational story took the first of many incredible twists when the group released a tape of Patty saying she had joined the SLA and had adopted the nom de guerre "Tania." The weird turns of the tale are truly astonishing -- the bank security cameras capturing "Tania" wielding a machine gun during a robbery; a cast of characters including everyone from basketball star Bill Walton to the Black Panthers to Ronald Reagan to F. Lee Bailey; the largest police shoot-out in American history; the first breaking news event to be broadcast live on television across the country; Patty's year on the lam; and her circuslike trial, after which the term "Stockholm syndrome" entered the lexicon. The saga of Patty Hearst highlighted a decade in which America seemed to be suffering a collective nervous breakdown. Based on more than a hundred interviews and thousands of previously secret documents, Toobin recounts the craziness of the times, portraying the lunacy of the half-baked radicals and the toxic mix of sex, politics, and violence that swept up Patty Hearst. He examines the life of a young woman who suffered an unimaginable trauma and then made the stunning decision to join her captors' crusade. Or did she?